Structural assessment & strengthening of the first singe-arch RC bridge in Sarajevo, BIH. (15th May 2021) - Ademović, Naida
Highlights: Rehabilitation of the oldest reinforced bridge in Sarajevo, Bosnia and Herzegovina. The synergy of visual inspection, nondestructive, and minor destructive tests. First usage of Infrared Thermography in BIH for detection of defects, etc. Numerical modeling and determination of the eigen frequencies and eigen modes. Risk carbonation modelling and predicting the remaining service life of the bridge. Abstract: Careva Ćuprija (Emperor's Bridge), located in the heart of the Old City in Sarajevo, was built in 1897. It was built as the first single-arch reinforced concrete bridge in Sarajevo with a span of 25.36 m. At that time, it was the largest structure of this type in the Austro-Hungarian monarchy. During its long life of 122 years, some rehabilitation work took place; however, the main design for its rehabilitation was done just in 2015. As the bridge is on the list of the national monuments of Bosnia and Herzegovina, ICOMOS Recommendations for the Analysis, Conservation and Structural Restoration of Architectural Heritage were followed. The current condition assessment of the bridge was used to identify the remaining service life of the bridge, the required type and level of treatments, and suitable time for applying repair and retrofitting methods. Visual inspection, nondestructive, and minor destructive tests were done with the goal to determine the mechanical characteristics of the built-in materials and define the state of the structure. The article discusses the used methods and obtained results, which were the basis for numerical model calculation and the creation of the rehabilitation design.